Conditioned medium from cultured cementoblasts upregulates amelotin gene expression via the SOCS3 signaling pathway - Nakayama, Yohei; Igarashi, Kazuma; Jin, Zhenyu; Yamaguchi, Arisa; Ganss, Bernhard; Ogata, Yorimasa (Journal of periodontal & implant science, 2025)
The junctional epithelium (JE) covers the cervical areas of developing or existing teeth. It can re-establish itself even after being removed during periodontal therapies, followed by wound healing. However, the mechanisms that can maintain this universally conserved structure are still unclear. The molecular mechanisms of JE homeostasis were investigated by altering levels of JE-specific genes in a telomerase immortalized human gingival epithelial cell line (TIGKs) by exposing TIGKs to conditioned medium (C-CM) from cultivated human cementoblasts. The mRNA and protein levels of JE-associated genes in TIGKs were examined using real-time polymerase chain reaction (PCR) and immunocytochemistry (ICC) after treatment with C-CM. The candidate pathways related to differential mRNA and protein expression were analyzed with a DNA microarray and identified using Kyoto Encyclopedia of Genes and Genomes and WikiPathways. Real-time PCR and ICC were conducted to confirm the changes in the expressions of candidate genes. mRNA levels and protein expressions of amelotin ( ) were upregulated after treatment with C-CM for 48 hours. DNA microarray analyses identified 595 genes that were upregulated >2-fold, and 820 genes that were downregulated >2-fold. C-CM promoted the expression of suppressor of cytokine signaling 3 and reduced the expression of an inactivator of Janus kinase 2. Both signaling molecules were found, using siRNA technology, to mediate the increase of mRNA and protein expression levels. The upregulation of in gingival epithelial cells by C-CM suggests that this regulatory pathway is associated with the homeostasis of JE structures by the cementum.